MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI GAYA STRADDLE MELALUI PERMAINAN LOMPAT GARUDA SISWA KELAS V SD NEGERI 01 SUKOREJO (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Based on outcome observation process learning athletic, especially for highjumping straddle style for student class five elementary school 01 sukorejo don’tgo yet well, because opportunity student action decrease. From the problem essaywriter try to improve student learning for high jump straddle style by playingmythical jump that purpose application concept high jump action straddle style byplaying for ad-dition activity student action. So can less scary of student andimprove student learning for high jumping straddle style. This type of research is aclass act using metode practice test. Subject of research is student class fiveelementary school 01 sukorejo numbered 43 students. Instrument that use to testobservation and obser-vation. Technic analysis the data used in this research is asstatistically descriptive comparative.Conclusions based on the results of research a class act, learning by approaching playmythical jump, can improve student learning for high jumping straddle style. Fromanalysis result on cycle I is knowed percentage of mastery learning numbered 79% by34 students, experienced improve in cycle II numbered 95% by mastery learning 41students and not complete learning numbered 5% by 2 students.